Rupture of hepatocellular carcinoma after transcatheter arterial chemoembolization: A case report - Hye Hyeon Moon; Hee Ho Chu; Ji Hoon Shin (Society of Gastrointestinal Intervention, 2021)
Transcatheter arterial chemoembolization (TACE) is one of the most common treatment options for patients with unresectable hepatocellular carcinoma (HCC). HCC rupture following TACE is a rare but potentially life-threatening complication. This report described a patient who experienced HCC rupture after TACE. The patient was successfully managed by transarterial embolization and staged liver resection. Large tumor size, superficial tumor location, exophytic growth of the tumor, and vascular lakes during TACE may be predisposing risk factors for HCC rupture after TACE.